The emergence of the Middle Palaeolithic in north-western Europe and its southern fringes. (8th August 2016) - Hérisson, David; Brenet, Michel; Cliquet, Dominique; Moncel, Marie-Hélène; Richter, Jürgen; Scott, Beccy; Van Baelen, Ann; Di Modica, Kévin; De Loecker, Dimitri; Ashton, Nick; Bourguignon, Laurence; Delagnes, Anne; et al.
Abstract: The nature of the Lower–Middle Palaeolithic transition has been one of the most debated questions in early Prehistory since the mid-20th century. The root of these debates lies primarily in how early prehistorians constructed chronological models, relying heavily upon index fossils. Such models have "artificial boundaries designed to provide structure to a complex record and, rather than being conceived of as permanent or real, should be frequently examined and revised (Corbey and Roebroeks, 2001)" (Monnier, 2006). In this paper, we will not focus our efforts on issues relating to nomenclature and systems of classification. Instead, we will focus on a time frame within which rapid behavioural and technological changes have been documented: the period between MIS 9 to 6. Working on a large scale, and taking account of all of north-western Europe and its southern fringes, a group of researchers working on the main sites from this period propose an assessment of current research on the emergence of the "Middle Palaeolithic". Using a rich corpus of archaeological sites, we discuss how humans occupied north-western Europe and its southern margins between MIS 9 to 6, focusing particularly on questions of taphonomy, conservation, chronology and environment, as well as reviewing the pattern of technological change within lithic assemblages. This overview of current research into the emergence of the Middle Palaeolithic will help to define future research paths and advance our understanding of this key period of human evolution.